Effect of tibial transverse transport on chronic lower extremity angiopathy: a protocol for a systematic review and meta-analysis. Issue 9 (7th September 2022) - Guo, Jiaxing; Bao, Huhe; Hu, He; Lideer,; Ni, Xiyu; Zhao, Yaxin; Sun, Guanwen
Abstract : Introduction: Chronic lower extremity angiopathy is a peripheral vascular disease that can result in disability and death. The tibial transverse transport (TTT) technique has been used to treat this disease in recent years. TTT's effect remains unclear owing to the lack of large samples and high-quality evidence. Therefore, this study aims to assess TTT's effectiveness and safety in chronic lower extremity angiopathy treatment. Methods and analysis: Relevant studies were acquired by searching the following databases: Cochrane Library, Embase, PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), China Science Technology Journal Database (VIP), Wanfang Data and Chinese Biomedical Literature Service System (CBM) until 20 September 2021. All randomised controlled trials and cohort studies on TTT for chronic lower extremity angiopathy will be included in this review. The primary outcomes will include the healing time and healing rate. The additional outcomes will include the Ankle Brachial Index, amputation rate, ankle skin temperature, Visual Analogue Scale, hospitalisation time, vascular endothelial growth factor, effective rate and complications. We will use Stata V.16.0 software and Review Manager V.5.3 software for meta-analysis. Subgroup and sensitivity analyses will be conducted, if necessary. Ethics and dissemination: This study was based on previous data. The medical ethics committee of Inner Mongolia People's Hospital, located in China waived the need for formal approval of this research, as this study did not fall under the principles of the Declaration of Helsinki. The results will be disseminated through peer-reviewed journals or relevant conferences. PROSPERO registration number: CRD42021281124.